Generation of baculovirus vectors for the high-throughput production of proteins in insect cells. - Possee, R; Hitchman, R; Richards, K; Mann, S; Siaterli, E; Nixon, C; Irving, H; Assenberg, R; Alderton, D; Owens, R; King, L (2008)
The baculovirus expression system is one of the most popular methods used for the production of recombinant proteins but has several complex steps which have proved inherently difficult to adapt to a multi-parallel process. We have developed a bacmid vector that does not require any form of selection pressure to separate recombinant virus from non-recombinant parental virus. The method relies on homologous recombination in insect cells between a transfer vector containing a gene to be expressed and a replication-deficient bacmid. The target gene replaces a bacterial replicon at the polyhedrin loci, simultaneously restoring a virus gene essential for replication. Therefore, only recombinant virus can replicate facilitating the rapid production of multiple recombinant viruses on automated platforms in a one-step procedure. Using this vector allowed us to automate the generation of multiple recombinant viruses with a robotic liquid handler and then rapidly screen infected insect cell supernatant for the presence of secreted proteins.